Protocolo simples para gravação acústica de formigas (Hymenoptera: Formicidae) e relações entre o comportamento de dominância numérica e características morfológicas nos sinais acústicos de formigas do solo - Vale, Érica (Instituto Nacional de Pesquisas da Amazônia - INPA, 2024)
Ants emit acoustic signals through percussion, using their bodies, or stridulation, through the stridulatory apparatus. Although studies analyse the behaviour of signal emission and use acoustic signals to identify ant species. It remains unclear how the emission of these signals influences resource dominance and, consequently, competition for food. In this dissertation, (i) I developed a simple and cost-effective protocol to record acoustic signals from ants in two ecological contexts: recruitment for resource use and distress calls; and (ii) I investigated how numerical dominance and the morphology of the stridulatory apparatus affect the emission of acoustic signals and the spectro-temporal parameters of ants in Central Amazonia. Among 70 species, 38 produced acoustic signals in both contexts. However, we used only 28 species from 7 subfamilies that were recorded for analysis. Our results suggest that, on average, combinations of microphones and recorders correctly identified the species 55 to 90% of the time, and the use of temporal parameters increased the precision of the models, indicating that acoustic signal analysis is more effective with spectral and temporal parameters. Regarding numerical dominance behaviour, acoustic signals are more frequently emitted by subordinate ants compared to dominant ants during foraging. The height of the stridulatory apparatus is correlated with the number of signal pulses, but the average interval between pulses is not related to the distance between ridges. Finally, we hope to contribute to studies of behaviour and the evolution of acoustic communication within the ant group. Keywords: acoustic signals, ants, Central Amazon, behavior, recruitment
Simple protocol for acoustic recording of ants (Hymenoptera: Formicidae) and relationships between numerical dominance behaviour and morphological characteristics in the acoustic signals of soil ants
Keywords: Bioacústica; Formigas